PENGELOLAAN WILAYAH LATIHAN TARUNA DI DESA JOGOMULYO KEC TEMPURAN KAB MAGELANG UNTUK MENDUKUNG PERTAHANAN - Titiek Herawati; Heri Wijanarko (PPM Sdirjianbang Akademi Militer, 2023)
This research is motivated by the mandate of the TNI Law Number 34 of 2004 which has been implemented by the Military Academy to play a positive role and contribute to building the nation through the management of cadets training areas. The aim of this study is to determine the joint action program of the Military Academy and the community, as well as the factors that drive and hinder them in supporting defense in Jogomulyo Village, Tempuran District, Magelang Regency. The research method used is a qualitative method with primary informants coming directly from the Head of Bagter Akmil and staff, the Village Community, Community Leaders, Village Officials, Babinsa, and Babinkamtibmas. The results of the study show that the joint action program of the Military Academy with the community in the training area of Jogomulyo Village is carried out through various activities, namely community service, academic programs, and social services. The key factor that drives the success of the program to support defense is the commitment of all Military Academy leaders to always maintain a harmonious relationship with the community through various empowerment programs to improve the welfare of the community in the cadets training area. The main obstacle factor is that there is still a perception that the Military Academy's activities are only temporary, so the village government and the community are not convinced that the joint action program of the Military Academy can help improve the welfare of the community, even though field data shows a great response and enthusiasm from the community towards these activities